Volume 2: Structures, Safety and Reliability 2011
DOI: 10.1115/omae2011-49919
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Transverse Cracks on Ultimate Strength of a Steel Plate Under Compression

Abstract: This study has been carried out on ultimate compressive strength of a cracked steel plate component, considering the effects of initial imperfections (transverse and longitudinal residual stresses and initial deflection, as well). The main objective of this paper is to numerically investigate the influence of crack location and crack length on ultimate strength of a steel plate under monotonic longitudinal compression. This investigation is performed through non-linear finite element (FE) analysis using ANSYS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Wang et al (2009a) investigated the influence of the multiple cracks on the ultimate load carrying capacity of the structural members where they concluded that the existence of the small disturbing cracks reduces the load capacity compared to a single cracked plate. Bayatfar et al (2011) studied the influence of the transverse cracks on the ultimate strength of a steel plate under uniaxial compression, accounting for the crack length and locations. They concluded that the most prominent crack location is the ones in the unloaded edges of the plates.…”
Section: Impact Of Crack-related Damagesmentioning
confidence: 99%
“…Wang et al (2009a) investigated the influence of the multiple cracks on the ultimate load carrying capacity of the structural members where they concluded that the existence of the small disturbing cracks reduces the load capacity compared to a single cracked plate. Bayatfar et al (2011) studied the influence of the transverse cracks on the ultimate strength of a steel plate under uniaxial compression, accounting for the crack length and locations. They concluded that the most prominent crack location is the ones in the unloaded edges of the plates.…”
Section: Impact Of Crack-related Damagesmentioning
confidence: 99%